Types of materials for frontalis sling surgery for congenital ptosis - Rosenberg, Jamie B (Cochrane Database Syst Rev, 2019)
BACKGROUND: Congenital ptosis is a drooping of one or both eyelids at birth, often due to poor development of the levator palpebrae superioris muscle. This can result in amblyopia, astigmatism, and ocular torticollis and therefore may necessitate surgical intervention in early childhood if visual development is compromised. Patients may have varied levels of levator function. Those with moderate to good function may elect to first attempt ptosis repair with external levator advancement or mullerectomy/Fasanella–Servat procedures. For those with poor function, those procedures are less likely to be effective, so they may undergo frontalis sling surgery, in which the tarsal plate is coupled to the frontalis muscle, so that movement of the brow and forehead result in movement of the eyelid. The optimal material to use in this surgery is unknown. OBJECTIVES: To evaluate the comparative effectiveness and safety of various materials used in frontalis sling surgery for congenital ptosis. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (which contains the Cochrane Eyes and Vision Trials Register) (June 2018), Ovid MEDLINE, Ovid MEDLINE E‐pub Ahead of Print, Ovid Medline In‐Process and Other Non‐Indexed Citations, Ovid MEDLINE Daily (January 1946 to 20 June 2018), Embase (January 1947 to 20 June 2018), PubMed (1948 to 20 June 2018), Latin American and Caribbean Health Sciences Literature Database (LILACS) (1982 to 20 June 2018), ClinicalTrials.gov (www.clinicaltrials.gov) and the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en). We did not use any date or language restrictions in the electronic search for trials. We last searched the electronic databases on 20 June 2018. SELECTION CRITERIA: We included randomized trials that compared one material to another for the treatment of congenital ptosis. DATA COLLECTION AND ANALYSIS: Two review authors independently completed eligibility screening, data abstraction, 'Risk of bias' assessment, and grading of the evidence. MAIN RESULTS: We identified three randomized trials that had compared four different materials, two materials in each trial. The studies included a total of 160 participants. The surgical procedures compared were polytetrafluoroethylene (Gore‐Tex), Ethibond suture, Mersilene mesh, and autogenous fascia lata. We judged all studies to be at unclear risk of bias due to incomplete reporting of methods and other methodological deficiencies. Because the three included studies compared different types of implants, we were unable to combine data in a meta‐analysis. The limited data preclude any conclusion regarding the optimal implant for frontalis sling surgery. In terms of the primary outcome of functional success, this was defined as widening of the opening between eyelids, assessed either by grade or by millimeter measurement. Bajaj 2004 showed that 93% of the Gore‐Tex group and 83% of the Ethibond group had a good or satisfactory outcome (as defined by investigators). Elsamkary 2016 reported that 78.1% of the autogenous fascia group and 61.8% of the Gore‐Tex group had a very good or good outcome. Salour 2008 did not include this type of grading system; they showed that the lid fissure increased 4.0 mm ± 1.46 mm in the Mersilene group and 3.13 mm ± 1.72 mm in the fascia lata group. In terms of adverse events, Bajaj 2004, which included 15 patients per group, showed no recurrence in the Gore‐Tex group and 1 in the Ethibond group; no need for removal in the Gore‐Tex group and 1 in the Ethibond group; and no infections in the Gore‐Tex group and 1 in the Ethibond group. Elsamkary 2016, which included 55 patients per group, had 3 recurrences in the fascia group and 6 in the Gore‐Tex group; no need for removal in either group; and 1 infection in the fascia group and 2 in the Gore‐Tex group. Salour 2008, which included 10 patients per group, had no recurrence, removals, or infections in either the Mersilene or the fascia group. AUTHORS' CONCLUSIONS: The three trials included in this review evaluated four materials for frontalis sling surgery. Assessment of these three studies does not allow us to identify the optimal material. Future randomized trials should be rigorously designed so as to identify the best treatment for this condition.